URGENSI PENDIDIKAN KEBENCANAAN BAGI SISWA SEBAGAI UPAYA MEWUJUDKAN GENERASI TANGGUH BENCANA - Siti Hadiyati Nur Hafida (Jurnal Pendidikan Ilmu Sosial, 2018)
Disasters are a phenomenon that is of concern to the public. Disaster events will not discriminate gender, age, ethnicity, religion and place. Often of disaster victims are vulnerable groups of people, such as: children, the elderly and women. Children have higher vulnerable than other groups. Elementary school children are groups that are very vulnerable because of the psychological weakness of students. This study aims to understand the urgency of disaster education for elementary school students. This research is a quantitative research with descriptive statistical analysis techniques. The results of the study show that disaster education is needed in realizing a disaster resilient generation. This is because elementary school students still have a low level of disaster preparedness. Knowledge, disaster preparedness plans, early warning systems and resource mobilization that owned by elementary school students are still below 60 or low category in preparedness disaster. The existence of disaster education will encourage elementary school students to act quickly and accurately in the face of disasters and increase empathy for disaster victims.